2017
DOI: 10.1074/jbc.m116.768143
|View full text |Cite
|
Sign up to set email alerts
|

An inducible amphipathic helix within the intrinsically disordered C terminus can participate in membrane curvature generation by peripherin-2/rds

Abstract: Peripherin-2/rds is required for biogenesis of vertebrate photoreceptor outer segment organelles. Its localization at the high-curvature rim domains of outer segment disk membranes suggests that it may act to shape these structures; however, the molecular function of this protein is not yet resolved. Here, we apply biochemical, biophysical, and imaging techniques to elucidate the role(s) played by the protein's intrinsically disordered C-terminal domain and an incipient amphipathic α-helix contained within it.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 68 publications
4
26
1
Order By: Relevance
“…In addition, previous studies demonstrated that Prph2 displayed membrane fusion activity, which led to the theory that Prph2 is involved in the shaping of the closed rim of fully developed discs in ROS [45,46]. Indeed, a function of Prph2 in inducing the curvature of the plasma membrane was observed in several studies [25,33,47,48]. While all these studies agree that Prph2 is involved in the generation of membrane curvature, they are contradictory in defining the exact region of Prph2 responsible for this activity.…”
Section: The Role Of Prph2 In Photoreceptor Outer Segment Morphogenesismentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, previous studies demonstrated that Prph2 displayed membrane fusion activity, which led to the theory that Prph2 is involved in the shaping of the closed rim of fully developed discs in ROS [45,46]. Indeed, a function of Prph2 in inducing the curvature of the plasma membrane was observed in several studies [25,33,47,48]. While all these studies agree that Prph2 is involved in the generation of membrane curvature, they are contradictory in defining the exact region of Prph2 responsible for this activity.…”
Section: The Role Of Prph2 In Photoreceptor Outer Segment Morphogenesismentioning
confidence: 98%
“…While all these studies agree that Prph2 is involved in the generation of membrane curvature, they are contradictory in defining the exact region of Prph2 responsible for this activity. Two studies pinpointed the membrane curvature inducing activity to an α-helix motif located in the C-terminus of Prph2 [47,48], while a third study argues that this motif is rather preventing membrane curvature than inducing it [25]. A recent study found evidence for a function of the tetraspanin core of Prph2 in generating membrane curvature while the C-terminus was unable to perform this function [33].…”
Section: The Role Of Prph2 In Photoreceptor Outer Segment Morphogenesismentioning
confidence: 99%
“…One of the easiest explanations for this result is that C-terminal ubiquitination is required for the LE targeting. Alternatively or additionally, since the C-terminal lysine residues belong to an amphipathic helix structure (Milstein et al, 2017), these lysines might play an Hrs-independent, structural role (e.g., membrane Figure 8. Delineating the endosomal expression of newly synthesized PRPH2 in vivo using TetOn-inducible system in transfected mouse cones.…”
Section: Multiple C-terminal Sorting Signals and Pathways Regulate Thmentioning
confidence: 99%
“…Chimera mapping studies performed in transgenic frog rods and transfected RPE-1 cells showed that the cytoplasmic C-terminal tail is required for the ciliary targeting of PRPH2 (Tam et al, 2004;Salinas et al, 2013;Tian et al, 2014). Ectopically expressed PRPH2 in AD293T and COS cells was absent from the plasma membrane and, instead, was distributed on internal membranes of unknown nature (Loewen et al, 2003;Conley et al, 2010;Khattree et al, 2013;Milstein et al, 2017;Salinas et al, 2017). Endoglycosidase sensitivity assays indicate that PRPH2 does not undertake the canonical Golgi-mediated secretory pathway (Connell and Molday, 1990;Tian et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The channel's subunits interact through sites located at the C-terminus of CNGα1 and N-terminus of CNGβ1 (Trudeau and Zagotta, 2002). The N-terminus of CNGβ1 is also responsible for binding calmodulin (Grunwald et al, 1998;Weitz et al, 1998) and peripherin-2 (Ritter et al, 2011;Milstein et al, 2017). The latter is conveyed through a relatively large GARP domain (Sugimoto et al, 1991;Colville and Molday, 1996), which can be sub-divided to a region containing four short proline-enriched repeats responsible for peripherin-2 binding (Ritter et al, 2011;Milstein et al, 2017) and a region of high glutamic acid content.…”
Section: Domain Structure Of the Rod Cng Channel Subunitsmentioning
confidence: 99%